Levels of reflection in student teacher digital portfolios: a matter of sociocultural context?. Issue 5 (3rd September 2021) - Chye, Stefanie; Zhou, Mingming; Koh, Caroline; Liu, Woon Chia
ABSTRACT: Reflection is recognised as a significant goal in teacher education. Digital portfolios have considerable potential for developing teacher reflective capacities, but more research is needed for documenting the content and quality of the reflections within it and for understanding the factors related to its occurrence. Many schemes of analyses have been developed. However, they do not accord sufficient attention to the situated nature of reflection and the sociocultural context within which reflection occurs. In this study, we seek to analyse and understand student teacher reflections as captured in digital portfolios. We propose using a lens that combines a framework on types of reflection with a situative perspective. Results suggest that student teachers do not typically reflect at deep levels, unless the situation legitimizes or privileges it, even if they may be able to do so. Findings are discussed in relation to contextual factors. It is surmised that student teacher reflections may be tied to the sociocultural context in which they learn and in which reflection is enacted.